The determinant, efficiency, and potential of Indonesian palm oil downstream export to the global market - Hansen Tandra; Arif Imam Suroso (Cogent Economics & Finance, 2023)
This study aims to investigate the determinants, efficiency, and potential of Indonesian palm oil downstream exports to the global market during 2012-2020. The stochastic frontier gravity model (SFGM) has been used to estimate the determinants, efficiency, and potential of palm oil downstream exports. The determinants show that the gross domestic product (GDP) importer, Indonesia's GDP per capita, the bilateral exchange rate, colonialization, and World Trade Organization (WTO) membership have a positive and significant impact on Indonesia's palm oil downstream exports. Nevertheless, there are negative and significant effects from Indonesia's GDP, geographical distance between Indonesia and trading partners, the importer's GDP per capita, and landlocked countries. In addition, the results reveal that no destination countries have maximum efficiency. Moreover, Indonesia has 148 countries that can be classified as trade potential growth in the global market. Therefore, there is a vast potential for the export of Indonesian palm oil downstream in the global market.
Keywords: 330; agriculture; business analytics; downstream products; stochastic frontier analysis; trade